The Helminth Parasite Heligmosomoides polygyrus Attenuates EAE in an IL-4Rα-Dependent Manner - White, Madeleine P. J.; Johnston, Chris J. C.; Grainger, John R.; Konkel, Joanne E.; O'Connor, Richard A.; Anderton, Stephen M.; Maizels, Rick M. (Frontiers in Immunology, 2020)
Helminth parasites are effective in biasing Th2 immunity and inducing regulatory pathways that minimise excessive inflammation within their hosts, thus allowing chronic infection to occur whilst also suppressing bystander atopic or autoimmune diseases. Multiple sclerosis (MS) is a severe autoimmune disease characterised by inflammatory lesions within the central nervous system; there are very limited therapeutic options for the progressive forms of the disease and none are curative. Here, we used the experimental autoimmune encephalomyelitis (EAE) model to examine if the intestinal helminth Heligmosomoides polygyrus and its excretory/secretory products (HES) are able to suppress inflammatory disease. Mice infected with H. polygyrus at the time of immunisation with the peptide used to induce EAE (myelin-oligodendrocyte glycoprotein, pMOG), showed a delay in the onset and peak severity of EAE disease, however, treatment with HES only showed a marginal delay in disease onset. Mice that received H. polygyrus four weeks prior to EAE induction were also not significantly protected. H. polygyrus secretes a known TGF-β mimic (Hp-TGM) and simultaneous H. polygyrus infection with pMOG immunization led to a significant expansion of Tregs; however, administering the recombinant Hp-TGM to EAE mice failed to replicate the EAE protection seen during infection, indicating that this may not be central to the disease protecting mechanism. Mice infected with H. polygyrus also showed a systemic Th2 biasing, and restimulating splenocytes with pMOG showed release of pMOG-specific IL-4 as well as suppression of inflammatory IL-17A. Notably, a Th2-skewed response was found only in mice infected with H. polygyrus at the time of EAE induction and not those with a chronic infection. Furthermore, H. polygyrus failed to protect against disease in IL-4Rα-/- mice. Together these results indicate that the EAE disease protective mechanism of H. polygyrus is likely to be predominantly Th2 deviation, and further highlights Th2-biasing as a future therapeutic strategy for MS.